2001
DOI: 10.1172/jci11297
|View full text |Cite
|
Sign up to set email alerts
|

CCR6-deficient mice have impaired leukocyte homeostasis and altered contact hypersensitivity and delayed-type hypersensitivity responses

Abstract: CCR6 expression in dendritic, T, and B cells suggests that this β-chemokine receptor may regulate the migration and recruitment of antigen-presenting and immunocompetent cells during inflammatory and immunological responses. Here we demonstrate that CCR6 -/-mice have underdeveloped Peyer's patches, in which the myeloid CD11b + CD11c + dendritic-cell subset is not present in the subepithelial dome. CCR6 -/-mice also have increased numbers in T-cell subpopulations within the intestinal mucosa. In 2,4-dinitrofluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
200
5

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 203 publications
(219 citation statements)
references
References 38 publications
14
200
5
Order By: Relevance
“…Two recent studies of CCR6-deficient mice confirmed this, and showed CCR6/CCL20 involvement in the control of leukocyte homeostasis in the gut [30,31]. In CCR6-deficient mice, CD11b + CD11c + myeloid DC are clearly decreased in the subepithelial dome of PP, since these cells are displaced mainly to the interfollicular region [30,31].…”
Section: P=000377; Two-tailed T-testmentioning
confidence: 75%
See 3 more Smart Citations
“…Two recent studies of CCR6-deficient mice confirmed this, and showed CCR6/CCL20 involvement in the control of leukocyte homeostasis in the gut [30,31]. In CCR6-deficient mice, CD11b + CD11c + myeloid DC are clearly decreased in the subepithelial dome of PP, since these cells are displaced mainly to the interfollicular region [30,31].…”
Section: P=000377; Two-tailed T-testmentioning
confidence: 75%
“…3). We and others showed that CCR6-deficient mice have increased numbers of TCR § g T cells within the small intestinal mucosa [30,31]. A real-time quantitative reverse transcription (RT)-PCR estimation of mRNA levels in mouse colonic mucosa revealed that basal CD8 transcript levels were six-to eightfold higher in CCR6-deficient mice than in the WT group.…”
Section: Ccr6-deficient Mice Are Protected Against Dss-induced Colitismentioning
confidence: 95%
See 2 more Smart Citations
“…C57BL/6 mice were originally purchased from the Jackson Laboratory. CCR6 À/À mice were generated in our laboratory [30] and backcrossed for nine generations onto the C57BL/6 background. The C57BL/6-Tg (ACTB-EGFP)1Osb strain was kindly provided by Dr. Masaru Okabe (Osaka University, Japan).…”
mentioning
confidence: 99%